Vocational Career Choice in Middle Childhood - Ningsih, Mirna Purnama; Barliana, Mokh. Syaom; Widiaty, Isma; Aryanti, Tutin (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2021)
Career choice can be made from an early age through introduction, habituation, and stimulation of children's interests. Parents need to recognize their child's interests related to future career choice. The study was conducted on 106 children aged 6-12 years to determine the careerchoices of children. Data collection was carried out by distributing online questionnaires (Googleform). Limited interviews were conducted with 5 mothers and children to explore children's career choices. The findings on gender show that boys tend to choose career specifics such as policemen, military troops and businessmen. On the other hand, girls tend to choose career specifics such as doctors and teachers. Career choice in children is influenced by 3 (three) factors, namely (1) the desire in the child, (2) interests/hobbies, (3) the profession of parents and family (role models)